Transfer Hydrogenation of Ethyl Levulinate to γ‐Valerolactone Catalyzed by Iron Complexes. Issue 4 (30th March 2015) - Dai, Nan; Shang, Rui; Fu, Mingchen; Fu, Yao
Abstract Conversion of biomass‐derived ethyl levulinate to γ‐valerolactone is realized by using homogeneous iron‐catalyzed transfer hydrogenation (CTH). By utilizing Casey's catalyst and cheap isopropanol as hydrogen source, γ‐valerolactone can be generated in 95% yield. Addition of catalytic amount of base is important to achieve good yield.